Formulation and In-Vitro Evaluation of Meloxicam Solid Dispersion using Natural Polymers. - Hiba R. Al-Hassani; Eman B. H. Al-Khedairy (College of Pharmacy University of Baghdad, 2021)
Meloxicam (MLX) is non-steroidal anti -inflammatory, poorly water soluble, highly permeable drug and the rate of its oral absorption is often controlled by the dissolution rate in the gastrointestinal tract. Solid dispersion (SD) is an effective technique for enhancing the solubility and dissolution rate of such drug.     The present study aims to enhance the solubility and the dissolution rate of MLX by SD technique by solvent evaporation method using sodium alginate (SA), hyaluronic acid (HA), collagen and xyloglucan (XG) as gastro-protective hydrophilic natural polymers. Twelve formulas were prepared in different drug: polymer ratios and evaluated for their, percentage yield, drug content,  water solubility,  dissolution, crystal lattice using powder X-ray diffraction (PXRD) and studies and Fourier Transform Infrared Spectroscopy (FTIR) for determination the drug-polymer interaction. All the prepared showed improvement of drug solubility except that prepared with HA. The best result was obtained with formula SD1 (MLX: SA 1:1) that showed a high percentage yield (97), high drug content (97.4±0.05) and increase in solubility compared to solubility of pure MLX with improved dissolution rate. the PXRD study revealed the conversion of the drug to amorphous form without chemical interaction according to FTIR results